Molluscicidal activity against Biomphalaria glabrata of the bioactive nanoemulsion of the essential oil of Thymus vulgaris Linn (Thyme) (Research, Society and Development, 2022)
This study evaluated the molluscicidal activity against the schistosomiasis-transmitting snail (Biomphalaria glabrata) of the nanoemulsion of Thymus vulgaris L. essential oil. The plant material was collected in the municipality of São Luís (MA). The essential oil was extracted by hydrodistillation at 100 °C for 3h, with chemical characterization performed by Gas Chromatography coupled to Mass Spectrometry (GC-MS). The nanoemulsions were prepared using the phase inversion method. For molluscicidal activity, the methodology recommended by the Who was performed, being the LC50 of the essential oil nanoemulsion for their action against the snail obtained by the Probit method. The major constituents found in Thymus vulgaris L. essential oil were carvacrol (27.35%) and thymol (24.12%). The molluscicidal activity of the essential oil nanoemulsion presented an LC50 of 15.04 mg L-1. The results indicate that the essential oil nanoemulsion evaluated is composed of substances that provide and encourage its application, due to its high potential for molluscicidal activity against Biomphalaria glabrata.